The Genomic Aftermath of Hybridization in the Opportunistic Pathogen Candida metapsilosis. - Leszek P Pryszcz; Tibor Németh; Ester Saus; Ewa Ksiezopolska; Eva Hegedűsová; Jozef Nosek; Kenneth H Wolfe; Attila Gacser; Toni Gabaldón (PLoS Genetics, 2015)
Candida metapsilosis is a rarely-isolated, opportunistic pathogen that belongs to a clade of pathogenic yeasts known as the C. parapsilosis sensu lato species complex. To gain insight into the recent evolution of C. metapsilosis and the genetic basis of its virulence, we sequenced the genome of 11 clinical isolates from various locations, which we compared to each other and to the available genomes of the two remaining members of the complex: C. orthopsilosis and C. parapsilosis. Unexpectedly, we found compelling genomic evidence that C. metapsilosis is a highly heterozygous hybrid species, with all sequenced clinical strains resulting from the same past hybridization event involving two parental lineages that were approximately 4.5% divergent in sequence. This result indicates that the parental species are non-pathogenic, but that hybridization between them formed a new opportunistic pathogen, C. metapsilosis, that has achieved a worldwide distribution. We show that these hybrids are diploid and we identified strains carrying loci for both alternative mating types, which supports mating as the initial mechanism for hybrid formation. We trace the aftermath of this hybridization at the genomic level, and reconstruct the evolutionary relationships among the different strains. Recombination and introgression -resulting in loss of heterozygosis- between the two subgenomes have been rampant, and includes the partial overwriting of the MTLa mating locus in all strains. Collectively, our results shed light on the recent genomic evolution within the C. parapsilosis sensu lato complex, and argue for a re-definition of species within this clade, with at least five distinct homozygous lineages, some of which having the ability to form hybrids.